Keabsahan Alat Bukti Elektronik dalam Perkara Perceraian: Analisis Yuridis dan Praktik di Pengadilan Agama - Rifky Akhmad Maulana Chaidir; Maria Rosalina; Raja Fikri Setiawan; Irwansyah Parulian Harahap (Lembaga Yasin AlSys, 2026)
Digital transformation has changed the dynamics of the law of evidence in Indonesia, including in divorce cases before the Religious Courts. Although Law Number 11 of 2008 concerning Electronic Information and Transactions has recognized electronic evidence as valid evidence, its implementation in religious court practice still faces epistemological and procedural obstacles. This study aims to analyze the legal status of electronic evidence, identify the gap between legal norms and judicial practice, and formulate appropriate legal reasoning for judges in verifying digital evidence. This study used a normative legal method with statutory and case approaches. The results show that juridically, electronic evidence has been recognized as an expansion of documentary evidence, but in practice, judges still tend to position digital evidence as supporting evidence. This disparity is influenced by the absence of uniform technical guidelines, limited digital forensic infrastructure, and the mindset of law enforcement officials that still prioritizes conventional evidentiary methods based on classical fiqh literature. The conclusion of this study affirms that the standardization of Digital Evidence Admissibility procedures is essential to minimize judicial subjectivity and legal uncertainty, while still observing the principle of prudence (ihtiyat) in Islamic law. The implications of this study emphasize the need to strengthen judges’ digital competence and renew evidentiary governance so that religious courts remain relevant, adaptive, and capable of delivering proportional justice in the era of information disruption.